An Examination the Use of Sugarcane Bagasse Ash as Cement Partial Substitutes in Concrete (International Journal of Innovative Research in Computer Science & Technology, 2023)
The strength and shrinkage of concrete  that is combined with sugarcane bagasse ash particles are  influenced by the size of the particles, as analyzed in this  research article. A higher amount of water is required  when utilizing Sugarcane Bagasse Ash (ScBA) in  concrete. The strength of the mixture created with fine  ScBA can be comparable to or greater than that of  standard concrete. The ScBA waste produced from  sugarcane contracts substantially as a consequence of the  presence of minute components within it. In this study,  the researchers utilized a material known as Sugarcane  Bagasse Ash (ScBA) to substitute cement in concrete.  The experiment involved testing the effectiveness of  ScBA (at different percentages: 0%, 5%, 10%, 15%, and  20%) in strengthening M20 concrete over a period of 28  days. They compared it to regular concrete. The extent to  which it could resist pressure and strain without snapping  was measured. The reason behind burning Sugarcane  waste (ScBA) for fuel is its ability to produce significant  amounts of heat. Cement can be supplemented with the  remaining ash after it has been burnt.
Keywords: Compressive strength Concrete; Split Tensile Strengt; Durability; Sugarcane Bagasse Ash; Workability